Management Of Bacterial Canker In Acid Lime Under Nursery Conditions (Journal of Plant Disease Sciences, 2021)
Citrus canker caused by Xanthomonas citri pv. citri is one of the most destructive and prevalent disease of acid lime in the Vidarbha region of Maharashtra. Three different agrochemicals, one botanical and two biocontrol agents efficacy investigated under nursery conditions against bacterial canker of acid lime and results revealed that among different chemicals evaluated Streptocycline + Copper oxychloride (Tank mix) preparation reduced the per cent leaves infection (29.62%), per cent leaf area infection (25.00%) and per cent shoot infection (27.86%) which is followed by Kasugamycine 5% + Copper oxychloride 45% (combi product).
Keywords: Agrochemicals; Bioagents; Citrus canker; Management, Nursery